2020
DOI: 10.1021/acs.jced.0c00020
|View full text |Cite
|
Sign up to set email alerts
|

Binary Mixtures of Aromatic Compounds (n-Propylbenzene, 1,3,5-Trimethylbenzene, and 1,2,4-Trimethylbenzene) with 2,2,4,6,6-Pentamethylheptane: Densities, Viscosities, Speeds of Sound, Bulk Moduli, Surface Tensions, and Flash Points at 0.1 MPa

Abstract: This study presents measured densities, viscosities, speeds of sound, surface tensions, and flash points and calculated bulk moduli of mixtures of 2,2,4,6,6-pentamethylheptane with C9H12 isomers (1,3,5-trimethylbenzene, 1,2,4-trimethylbenzene, and n-propylbenzene). The densities, speeds of sound, bulk moduli, and surface tensions increase and viscosities decrease as the mole fraction of the C9H12 isomer increases. Flash points decreased, remained the same, and increased as the amounts of n-propylbenzene, 1,3,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…Before measuring the viscosities of solutions, the Ubbelohde viscometer was calibrated using ultrapure water and a standard viscosity liquid (S3­(L), Anton Paar, Austria) at different temperatures. The viscosity η of solutions can be calculated by the following formula according to Poiseuille’s law where ρ is the density of solution, c and b are the viscosity constants of the Ubbelohde viscometer, and t is the flow time.…”
Section: Methodsmentioning
confidence: 99%
“…Before measuring the viscosities of solutions, the Ubbelohde viscometer was calibrated using ultrapure water and a standard viscosity liquid (S3­(L), Anton Paar, Austria) at different temperatures. The viscosity η of solutions can be calculated by the following formula according to Poiseuille’s law where ρ is the density of solution, c and b are the viscosity constants of the Ubbelohde viscometer, and t is the flow time.…”
Section: Methodsmentioning
confidence: 99%
“…26,31,47,48 Simulations of n-propylbenzene, 1,2,4-trimethylbenzene, and 1,3,5-trimethylbenzene showed that the pure aromatic compounds were oriented with their benzene rings in both parallel (angles near 0°) and perpendicular arrangements, with the long-chain propyl compound having a larger probability of the in-parallel configuration than the others. 26 In mixtures with iso-dodecane, the probability of finding these molecules with their aromatic rings in parallel arrangements increased in comparison to that in the pure aromatic liquids. 26 This alteration in the orientation of the alkylbenzene molecules in the presence of iso-dodecane was likely to contribute to the positive excess molar volumes determined experimentally for these binary mixtures.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…26 In mixtures with iso-dodecane, the probability of finding these molecules with their aromatic rings in parallel arrangements increased in comparison to that in the pure aromatic liquids. 26 This alteration in the orientation of the alkylbenzene molecules in the presence of iso-dodecane was likely to contribute to the positive excess molar volumes determined experimentally for these binary mixtures. For mixtures of n-alkylbenzenes with nhexadecane, Morrow et al reported changes in molecular orientation of the aromatic ring in the benzene and toluene in the presence of n-hexadecane, but for ethyl-, n-propyl-and nbutylbenzene, this change in the aromatic ring orientation was small.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
See 1 more Smart Citation
“…A common theme in the successful entries was the use of an allatom force field, which has been shown previously to be important for accurate viscosity predictions of long-chain hydrocarbons. 28 Several other studies have used MD simulations to investigate the viscosity of hydrocarbon mixtures; [37][38][39][40][41][42][43][44][45][46] however, only a few of these have calculated viscosities at elevated pressure. In a recent study, Verma et al 42 studied the viscosity of n-octane + n-dodecane and n-hexadecane + ndecylbenzene binary mixtures up to 200 MPa using the Green-Kubo method.…”
Section: Introductionmentioning
confidence: 99%